ALASAN HARGA DIRI PADA PRAKTEK CAROK (TINJAUAN HAM DAN HUKUM ISLAM) - Bagis Syarof; Faiq Tobroni (IAIN Ambon, 2020)
Conflicts between humans often occur. The solution also varies. Some times it is done through a good conversation, or it can be with a fight, and even through legal channels. There is something interesting about one of the tribes in Indonesia, namely Madura. When experiencing conflict with other people, they take the solution through carok (fight with sickles). The common cause of carok is conflict related to the throne, wealth and women. The enemies are considered to lower their self-esteem, when it has disturbed these three things. As a consequence, carok becomes a solution to restore self-esteem that is lowered. This paper is the result of qualitative research with literature approach. This study questions how the reasons for self-esteem in the practice of carok in terms of Islamic law and human rights? As a finding, the authors conclude that although Islamic law and human rights do justify the protection of self-esteem for everyone, the reasons for self-defense through carok are not justified in Islamic law because they violate qishos law and are also not justified in human rights because they are not under national law. Keywords: carok, islamic law, human rights.